Modeling of ring resonators as optical Filters using MEEP - Matere, I. M.; Waswa, D. W.; Tonui, J; Boiyo, Kiboi (My University, 2016)
Ring Resonators are key component in modern optical networks. Their size allows high density integration in optical photonic circuits due to the use of high index contrast. Ring Resonators based filters in wavelength division multiplexing are considered as one example in this technology. In this study, we theoretically demonstrate Ring resonators for optical filter applications. Coupling a closed loop resonator with a straight waveguide using evanescent coupling, leads to a filter behavior of a new structure. By using Mit Electromagnetic Equation Propagation (MEEP) the transfer functions, resonance frequency of 1.45 x 1015 rad/s, resonance wavelength of 1.2955 μm and characteristics of a tunable optical filter showed a good agreement between analytical and simulation based results. This work is of great interest in designing add/drop in wavelength division multiplexing (WDM) which will improve the selection of the optical signal and data fibre to home (FTH).
Keywords: Free spectral Range (FSR); Finesse (F); Quality factor (Q); Tunable filter